Hubungan Demografi dan Pengetahuan tentang Penggunaan Obat Tradisional: Studi pada Masyarakat Banjar X, Kabupaten Gianyar - Megawati, Fitria; Anita Dewi, Ni Luh Kade Arman; Ekayanti, Ni Luh Firda (Usadha, 2025)
The use of traditional medicine in the modern era is gaining popularity, as it is often considered to have fewer side effects compared to modern medicine. Traditional remedies have been used for generations by communities as an alternative approach to maintaining health. This study aims to assess the level of community knowledge and to analyze the relationship between demographic factors (age, gender, education, occupation, and income) and knowledge regarding the use of traditional medicine. A descriptive-analytic design was employed, with data collected through door-to-door questionnaires. The study was conducted in Banjar X, Gianyar Regency, with a population of 619 households. A total of 87 respondents were selected based on inclusion and exclusion criteria. The findings revealed that the community’s level of knowledge was categorized as good (52.9%). Analysis of demographic factors and knowledge indicated associations between age (p = 0.079), income (p = 0.076), and education (p = 0.064) with knowledge of traditional medicine use. Thus, certain demographic characteristics—namely age, education, and income—were found to be significantly related to the level of community knowledge in using traditional medicine in Banjar X. These results highlight the important role of demographic factors in shaping public health literacy concerning traditional medicine.